Selected Properties of Wood-Based Panels as a Function of Raw Material, Applied Treatment and Exposure Conditions - Emilia-Adela Salca (Advanced Research in Biological Science Vol. 2, 2023)
Wood based-panels are products in which wood is present in the form of chips, strips, veneers, strands or fibres. They were originally developed to provide utility panel materials with uniform properties. These panels are versatile products with a wide variety of end uses due to the features they present. They have a long history of continuous optimization. However, there is still a long way to be fully developed, new panels are ongoing researched and produced. In this chapter selected properties of particleboards, oriented strand boards (OSB) and fibreboards (MDF) under different treatments and exposure conditions are approached. The findings of various studies presented in this work could have practical applications for a better capitalization of wood resource in furniture manufacturing and to obtain value-added products.